Water entry of cylinders and spheres under hydrophobic effects; Case for advancing deadrise angles. (1st January 2017) - Korkmaz, Fatih C.; Güzel, Bülent
Abstract: The results of an experimental investigation of water entry of spherical and cylindrical shaped objects with hydrophobic surfaces are presented in this work. The test specimens have a varying deadrise angle. Drop tests have been set up for studying slamming by dropping test objects from various heights toward water surface. Different fluid dynamics phenomena like jet formation, cavity formation, water splashing and flow separation on solid surfaces are investigated and compared with under hydrophobic effects. From digital images captured using a high speed camera, pileup coefficients and splash velocities are measured. It is observed that flow separation occurs earlier with hydrophobic surfaces causing no pressure pulse occurrence on the solid surface at larger penetration depths. Hydrophobicity also causes larger pileups with faster jet flows indicating more kinetic energy transference to the fluid. Along with high speed imaging, the impact loads are calculated and compared with when hydrophobicity is present via strain gauge measurements. It is found that the peak strain values during slamming are smaller with hydrophobic surfaces promoting a reduction in the impact forces while distributing the pressure pulses on a larger wetted area. Highlights: More kinetic energy is transferred to jet flow and pileups under hydrophobic effects. Smaller impact forces are noted under hydrophobic effects. Force distribution on a larger wetted area with larger penetration depth is observed. Hydrophobicity promotes early flow separation from solid surface. Hydrophobicity creates larger cavity behind the object.